ANALISIS USAHA PEMANFAATAN LIMBAH KULIT KAYU GERGAJIAN DI UD. SUMARNI KECAMATAN SUKAMAJU KABUPATEN LUWU UTARA - Dewi Marwati Nuryanti (Journal TABARO Agriculture Science, 2017)
Utilization of waste lumber skin in addition to increasing revenue can also make efficient use of natural wood and wood folk and reduce environmental damage. Waste processing of lumber skin held in UD. Sumarni starting from procurement of raw materials, sawing, drying, sorting, packaging and marketing. Waste  lumber skin used as raw materials generally durian (Durio zibethinus) wood and some kind of small porous timber such as teak (Tectona grandis L.F), Uru (Elmerrillia sp), Jabon (Anthocephalus sp) with a minimum length of 1 (one) meter, a minimum thickness of 1.5 cm, and is not easily cracked / broken. Within a year the amount of Waste lumber skin than can be processed by UD.Sumarni as  many as 360 trucks equivalent to 5.184 sm. Of waste treatment is obtained revenue amounted to Rp. 890.400.000,- with a total cost of Rp. 744.530.000,- in order to obtain a gain of Rp. 145.870.000,- per year or Rp. 458.710,69 per m³ and break even point was 67.78 m³ or Rp. 188.190.476,19 per year. In order for the processing of  waste lumber skin got gain, then UD.Sumarni should result in the production of over 67,78 m³ per year or earn an income above Rp. 188.190.476,19 per year.